What change of epoch brings into the basic principles of school: authority, oppression, individuation? - Todorović, Milorad V. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Every historical epoch - the time interval bounded by upheavals with "epochal significance" - has the characteristic patterns, the principles of internal development and organization. While the old epoch, by the nature of things - subsequently, with "hindsight", always perceived, more or less the same, as a form, a new epoch is never with so clear-cut contours and expressions and therefore it is difficult to describe, understand or predict. It is easy to assume that old form begins to collapse because of the internal rush of content that somehow become inappropriate, but, if our ability of understanding were higher, it would not be hard to spot patterns in the evolutionary chain and know how these upcoming content will take shape into the new form of the forthcoming, starting epoch. If the analysis of the new forms focus just on the pathological form, it seems that it is not difficult to assume that the reduction and lifting the ban in the area of ​​sexuality – hysteria will certainly make way to other pathological forms, primarily those related to difficulties with identity. Similarly, it can be assumed that in the new pathological forms a central place occupy the feeling of personal emptiness, together with the aggressiveness that goes to the brutality. In any case, a new era never begin with form creation. Each form takes time to be shaped, stabilized and as such to be longer-lasting. Because the process leads (changes) to form and a form occurs "definitely" only after the process is complete. While waiting for setting sufficiently general practical rules and principles, the entire educational system and in particular the school system can become a place of creation children problem and not solving it, precisely because of his absolute legitimacy of the principle of reality. Since it could not be more important aim of education of avoiding that instruction, tuition, influences and restrictions that fall on a relatively weak ego - act as trauma and launch a massive repression mechanism that creates a tendency to later disease, the strategy of education must be more than ever previously based on the theory of depth psychology. Bearing in mind that current position of authority is not clear, immediate execution of the main task of education is hindering, prohibits and suppresses impulses - a task that has existed at all times - is faced with no small problems. The child should first of all master his instincts, and do it in a socially acceptable manner. Therefore, we ought to point out that the path between the Scylla permission and Haridbe prohibition can not be found if psychoanalysis is not applied on the education.